2018
DOI: 10.1051/0004-6361/201732232
|View full text |Cite
|
Sign up to set email alerts
|

Using the CIFIST grid of CO5BOLD 3D model atmospheres to study the effects of stellar granulation on photometric colours

Abstract: Context. The atmospheres of cool stars are temporally and spatially inhomogeneous due to the effects of convection. The influence of this inhomogeneity, referred to as granulation, on colours has never been investigated over a large range of effective temperatures and gravities.Aim. We aim to study, in a quantitative way, the impact of granulation on colours.Methods. We use the CIFIST (Cosmological Impact of the FIrst Stars) grid of CO5BOLD (COnservative COde for the COmputation of COmpressible COnvection in a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Both photometric surveys can be usefully complemented by the Gaia spectrophotometry. Furthermore, when the Gaia RVS photometry becomes available it has been shown that it can provide a very powerful metallicity diagnostic for F,G and K stars (Bonifacio et al 2018a). It thus seems that a pre-selection of metal-poor giants is indeed possible.…”
Section: The Observational Strategymentioning
confidence: 99%
“…Both photometric surveys can be usefully complemented by the Gaia spectrophotometry. Furthermore, when the Gaia RVS photometry becomes available it has been shown that it can provide a very powerful metallicity diagnostic for F,G and K stars (Bonifacio et al 2018a). It thus seems that a pre-selection of metal-poor giants is indeed possible.…”
Section: The Observational Strategymentioning
confidence: 99%
“…For each calibration used to derive the effective temperature, we derived the corresponding surface gravity from the Stefan-Boltzmann relation using the distances from the parallaxes provided by Gaia DR2 and the stellar absolute luminosity, derived from the Gaia G band and a bolometric correction based on three-dimensional (3D) model atmospheres (Bonifacio et al, 2018). We assumed the mass of each star according to its tem- perature, by looking at the isochrones.…”
Section: Stellar Parametersmentioning
confidence: 99%
“…Considerable efforts have been made in recent years to evaluate these effects, which strongly depend on the properties of the stars. The effects of the convective shift on the wavelength of all the spectral lines observed in all kinds of late-type stars will be taken into account by using synthetic spectra computed with 3D hydrodynamical models (Bonifacio et al 2018;Chiavassa et al 2018). The determination of RVs is also affected by the gravitational redshift that results from the deformation of the light path in the potential of the observed star.…”
Section: Radial Velocity Zero Pointmentioning
confidence: 99%